POTENSI TANAMAN HERBAL SEBAGAI STIMULAN SISTEM SARAF PUSAT: LITERATURE REVIEW ARTICLE - Suri, Nurma; Oktoba, Zulpakor; Yulianti, Mega Intan (Jurnal Buana Farma, 2024)
Energy drinks are consumed as supplement to increase energy and reduce fatigue. Herbal medicine has proven reduce fatigue in the body. This literature review aims to determine the types of herbal medicine that have properties as stimulants. This study used descriptive methode using the Population-Intervention-Controling-Outcome Framework. A literature search on studies published in the period 2012-2022 on the Google Scholar and Pub-Med using the keywords: stimulant, central nervous system, tonic, and herbal. Articles that cannot be accessed in full and herbal medicine that are not original from Indonesia will be excluded as samples. There were 1937 articles obtained based on the keywords used, a total of 91 articles met the inclusion criteria and 60 articles were excluded. Based on 30 articles reviewed, there are 31 types of herbal medicines that can increase stimulants with the most family is zingiberaceae and piperaceae. The combination of plant has a better stimulant effect than using the single plants. In vivo test method with the swimming endurance test as the most widely used. Flavonoid, alkaloid and terpenoid compounds are most likely to be effective as stimulants which have the same mechanism with caffeine through inhibition of Adenosine A1 receptors. This study shows there are 31 herbal medicine that have the potential to increase stimulants. Secondary metabolites which stimulant effects are flavonoids, alkaloids and terpenoids